Triggered slip along the San Andreas fault after the 8 July 1986 North Palm Springs earthquake - Williams, Patrick L. (2013)
In addition to minor surface cracks in the region of the 8 July 1986 North Palm Springs earthquake, minor aseismic surficial rupture occurred along three segments of the San Andreas fault, 44 to 86 km southeast of the epicenter. Data from a creepmeter and a tiltmeter at one locality suggest that triggered slip occurred coseismically beneath the instruments but took 33 hr to propagate to the surface. That slippage occurred coseismically at depth favors mechanisms for triggered slip that involve dynamic or static strain changes rather than creep migrating from the source region.